Associations between hand osteoarthritis, obesity and lipid metabolism: a cross-sectional study of the Halland County Osteoarthritis (HALLOA) cohort - Elisabeth Brogren; Maria Andersson; Melker Westenius; Jenny Wittrup; Malin Zimmerman (BMC Musculoskeletal Disorders)
Abstract Background To determine whether obesity and markers of lipid metabolism are associated with radiological hand osteoarthritis (OA) in the Halland County Osteoarthritis (HALLOA) cohort. Methods In this cross-sectional study, we included 231 participants aged 30–65 from the HALLOA cohort, which began in 2017 and is ongoing. Hand OA was defined as ≥ 2 joint groups (distal interphalangeal, proximal interphalangeal, and carpometacarpal I) with Kellgren-Lawrence grade ≥ 2. The severity of hand OA was classified in terms of the number of affected joint groups (moderate hand OA 2–4 joint groups, severe hand OA 5–6 joint groups). Metabolic profile, including body mass index (BMI), bioimpedance, waist circumference, blood pressure, serum leptin, total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglycerides, were obtained. Multicollinearity was assessed with Pearson’s correlation and associations with logistic regression analyses adjusting for age, HDL-cholesterol, and central obesity. Results Two-thirds of the participants were women, and 91 (39%) had hand OA. We found a relationship between LDL-cholesterol and prevalent hand OA in women with an odds ratio of 1.7 (95% CI 1.1–2.6) and an association between LDL-cholesterol and severity of hand OA in women; odds ratio for no hand OA vs. moderate hand OA was 1.6 (95% CI 1.0-2.4) and for no hand OA vs. severe hand OA 2.5 (95% CI 1.2–4.9). There were no significant relationships between hand OA and obesity or serum leptin levels. Conclusion Circulating LDL-cholesterol levels were associated with the prevalence and severity of hand OA in women but not men. Trial registration ClinicalTrials. Gov (NCT04928170), Date of registration: 2017-12-20.